1989
DOI: 10.1111/j.1365-2621.1989.tb04648.x
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Sodium Chloride by Modified Potassium Chloride (Cocrystalized Disodium‐5′‐Inosinate and Disodium‐5’‐Guanylate with Potassium Chloride) in Fresh Pork Sausages: Acceptability Testing using Signal Detection Measures

Abstract: Experiments were developed to evaluate the effect of replacement of NaCl with modified KCI on the hedonic ratings for fresh pork sausage patties. Results clearly indicated that the replaccmcnt of up to 75% (w/w) of the salt by modified KC1 were significantly well accepted. The incorporation of any level of MSG decreased the overall acccptante level of modified KCI to 50% (w/w). With the incorporation of two additional spice levels, the acceptance level of modified KCI did not improve much beyond 75% (w/w).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
4

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 5 publications
1
14
0
4
Order By: Relevance
“…The formulations T 2 and T 3 presented values for the aroma attribute that are significantly higher than those of the control, and the pleasant smell of the added seasonings was enhanced (Table 5). In the control difference test, the assessors did not detect any decrease in the salty taste or increase in the astringency in the treatments with replacement of NaCl by KCl compared to the control, as expected based on literature data (TERRELL, 1983;PASIN et al, 1989). Similar to what was observed in the acceptance test, the assessors evidenced an improvement in treatments T 2 and T 3 giving higher scores to the attribute "seasoning taste" (Table 6).…”
Section: Sensory Analysissupporting
confidence: 74%
“…The formulations T 2 and T 3 presented values for the aroma attribute that are significantly higher than those of the control, and the pleasant smell of the added seasonings was enhanced (Table 5). In the control difference test, the assessors did not detect any decrease in the salty taste or increase in the astringency in the treatments with replacement of NaCl by KCl compared to the control, as expected based on literature data (TERRELL, 1983;PASIN et al, 1989). Similar to what was observed in the acceptance test, the assessors evidenced an improvement in treatments T 2 and T 3 giving higher scores to the attribute "seasoning taste" (Table 6).…”
Section: Sensory Analysissupporting
confidence: 74%
“…In meat products, R-index values greater than 50% indicate a higher hedonic rating (Pasin et al 1989). Added pineapple fiber had no effect on sausage firmness (R-index = 50%), whereas the higher R-index value close to 100% (90.29%) indicated that samples formulated with cactus pear fiber were clearly preferred by judges (Lee and Van Hout 2009).…”
Section: R-indexmentioning
confidence: 99%
“…The literature contains reports that the ratio of sodium to glutamate affects palatability of the solution (Chi & Chen, 1992;Halpern, 2000;Okiyama & Beauchamp, 1998;Pasin et al, 1989) but the effect of components like glutamate on perceived saltiness are not so well-documented. One report describes a soup system which was formulated with either NaCl or with NaCl and monosodium glutamate and then tested by a sensory panel to determine which formulations were equi-salty (Yamaguchi & Takahashi, 1984).…”
Section: Time -Intensity Overall Saltiness Score and Data Analysismentioning
confidence: 99%